EXISTENTIAL PARADIGM OF B. ANTONENKO-DAVIDOVICH PROSE - Kuzmin, М. R. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article outlines the most characteristic features of existentialism as an artistic phenomenon in the world literature, emphasizes the features of Ukrainian existentialism, which is characterized by its national peculiarity. The special attention is devoted to the particularities of the perception of revolutionary reality by various types of characters of B. Antonenko-Davidovich's early period creativity. A separate emphasis is placed on the contrast between the two types of consciousness, which in the author’s works forms a kind of opposition and is the link that connects the works of the early and post-rehabilitation periods of the author's prose. On the background of the “Vartovyi Chapenko” (“Guard Chapenko”) essay, a transitional element between the two types formed by the revolutionary heroes is drawn, whose tragedy determined the misunderstanding of the true essence of the Bolshevik system. On the basis of the “Synia Voloshka” (“Blue Flute”) story an existential model of self-understanding in the world is analyzed; it was discovered that such a way of self-identification is oppositional to the requirements of the contemporary society; it focuses on the destruction of the bright ideals and the appeal of hero-defenders to such existential categories as "alienation", "death", "absurdity". It has been proved that existential motives become distinctive markers of B. Antonenko-Davidovich's prose.